Study the satisfaction of the beneficiaries of the services of Dar Al-Fajr for the care and rehabilitation of orphans from a mothers' point of view - Amrullah, Abdul-Malik Karim; Bakhabazy, Yaser Saleh Mahfoudh (Journal of Educational and Psychological Sciences, 2021)
The study aimed to identify the extent to which the mothers of the beneficiaries are satisfied with the services provided to them by Dar Al Fajr for the care and rehabilitation of orphans, which are: social care, health care, psychological care, cultural and religious care, educational care, the field of training and employment, financial care, and to achieve the objectives of the study The researcher followed the descriptive approach, and a sample consisting of (61) mothers of orphans was selected. The study tool consisted of a questionnaire consisting of (34) items distributed on seven axes: The results of the study concluded that the degree of mothers ’satisfaction with the services provided by Dar Al Fajr for the care and rehabilitation of orphans To a very large extent, where the arithmetic averages came on the social side between (4.80) and (4.57), and on the health side came the arithmetic averages between (4.72) and (4.55), and on the psychological side, the arithmetic averages ranged between (4.80) and (4.54), and on the cultural and religious side, the arithmetic averages came between (4.93) and (4.65), and on the educational side, the arithmetic averages ranged between (4.98) and (4.45), and with regard to the training and employment side, the arithmetic averages ranged between (4.70) and (4.44), and on the financial side, the arithmetic averages ranged between (4.81) and (4.75), due to their awareness and appreciation of the responsibility that they have and do well, in light of the above, the researcher recommended presenting seminars and lectures to the workers in the house to raise awareness about Fadl Ensuring orphans according to Islamic law, and increasing attention to training the workers in the home during service and providing them with new educational, psychological and social data that will benefit the residents there.
Keywords: satisfaction of the beneficiaries; Dar Al-Fajr for the care and rehabilitation of orphans